2018
DOI: 10.3390/nu10030307
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dietary Magnesium Intake and Higher Magnesium Status Are Associated with Lower Prevalence of Coronary Heart Disease in Patients with Type 2 Diabetes

Abstract: In type 2 diabetes mellitus (T2D), the handling of magnesium is disturbed. Magnesium deficiency may be associated with a higher risk of coronary heart disease (CHD). We investigated the associations between (1) dietary magnesium intake; (2) 24 h urinary magnesium excretion; and (3) plasma magnesium concentration with prevalent CHD in T2D patients. This cross-sectional analysis was performed on baseline data from the DIAbetes and LifEstyle Cohort Twente-1 (DIALECT-1, n = 450, age 63 ± 9 years, 57% men, and diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
0
19
1
Order By: Relevance
“…Thus, it has been estimated that 40%-50% of adults do not achieve the average dietary intake (ADI) [14][15][16]. Although it is problematic to find good indicators of so-called magnesium deficiency in organisms [14,[17][18][19][20], a number of studies have been undertaken to reveal the percentage of the population that presents hypomagnesemia and its negative repercussions on health [20][21][22][23]. Many studies carried out on various populations have generally supported the protective role that magnesium plays when faced with different human health problems [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been estimated that 40%-50% of adults do not achieve the average dietary intake (ADI) [14][15][16]. Although it is problematic to find good indicators of so-called magnesium deficiency in organisms [14,[17][18][19][20], a number of studies have been undertaken to reveal the percentage of the population that presents hypomagnesemia and its negative repercussions on health [20][21][22][23]. Many studies carried out on various populations have generally supported the protective role that magnesium plays when faced with different human health problems [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of chronic latent magnesium depletion (hypomagnesaemia), defined as <0.75 mmol/L in blood [ 22 ] is not new, yet deficiency of magnesium remains an often unrecognized and widespread reality in the modern world [ 23 ]. Furthermore, insufficient magnesium is linked to a spectrum of clinical afflictions, including arrhythmias [ 24 ], hypertension [ 25 , 26 ], coronary artery disease [ 27 , 28 , 29 ], migraines/headaches [ 30 ], osteoporosis [ 31 , 32 , 33 ] and type 2 diabetes mellitus (T2DM) [ 28 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…51 A recent study concluded that a higher magnesium supplement coupled with a higher serum magnesium level appear negatively correlated to the prevalence of coronary heart disease in diabetic patients. 52 Results from other clinical trials also pointed that the heart rate variability, 53 arterial elasticity 54 and the survival rate as well as the clinical symptoms 55 in heart failure patients are improved through magnesium supplementation. In the present study, the protective effects of MgSO 4 is similar to DSW indicating that the anti-inflammation effects of DSW can be partly due to rich in magnesium.…”
Section: Discussionmentioning
confidence: 97%
“…Low serum magnesium level can cause various diseases, such as hypertension, type 2 diabetes, ventricular arrhythmia, and heart failure . A recent study concluded that a higher magnesium supplement coupled with a higher serum magnesium level appear negatively correlated to the prevalence of coronary heart disease in diabetic patients . Results from other clinical trials also pointed that the heart rate variability, arterial elasticity and the survival rate as well as the clinical symptoms in heart failure patients are improved through magnesium supplementation.…”
Section: Discussionmentioning
confidence: 99%